Wellness Innovation Lab : Workshop Guidebook - Leading English Education and Resource Network (LEARN); Percolab Coop (2023)

QFHSA News - Quebec Federation of Home and School Associations (QFHSA) (2022)

Resolution 2022-03 : A Call to Suspend and Amend Law 21 - Quebec Federation of Home and School Associations (QFHSA) (2022)

Resolution 2021-07 : Addressing the Issue of the Teacher Shortage in Quebec - Quebec Federation of Home and School Associations (QFHSA) (2021)

QFHSA News Bulletin - Quebec Federation of Home and School Associations (QFHSA) (2021)

QFHSA News - Quebec Federation of Home and School Associations (QFHSA) (2021)

QFHSA News - Quebec Federation of Home and School Associations (QFHSA) (2021)

Tips for an Engaging Online Workshop - Leading English Education and Resource Network (LEARN) (2020)

Tips for an Engaging Online Workshop - Leading English Education and Resource Network (LEARN) (2020)

[Update to Parents Regarding Minister of Education's Announcement of Three Additional Planning Days for Teachers] - English Parents' Committee Association (EPCA) (2020)

Le Canada de Minnie H. Bowen : Cahier de l'enseignant pour le primaire - Eastern Townships Resource Centre (ETRC) (2019)

Le Canada de Minnie H. Bowen : Cahier de l'enseignant pour le secondaire - Eastern Townships Resource Centre (ETRC) (2019)

Loyalistes : Le développement des Cantons-de-l'Est par les Loyalistes : Cahier de l'enseignant pour le primaire - Eastern Townships Resource Centre (ETRC) (2019)

Loyalistes : Le développement des Cantons-de-l'Est par les Loyalistes : mythe ou réalité ? : Cahier de l'enseignant pour le secondaire - Eastern Townships Resource Centre (ETRC) (2019)

Loyalists : The Development of the Eastern Townships by the Loyalists : Teacher's Workbook - Eastern Townships Resource Centre (ETRC) (2019)

Loyalists : The Development of the Eastern Townships by the Loyalists : Teacher's Workbook for Elementary School - Eastern Townships Resource Centre (ETRC) (2019)

Loyalists : The Development of the Eastern Townships by the Loyalists : Teacher's Workbook for Highschool - Eastern Townships Resource Centre (ETRC) (2019)

Minnie H. Bowen's Canada : Teacher's Workbook for elementary school - Eastern Townships Resource Centre (ETRC) (2019)

Minnie H. Bowen's Canada : Teacher's Workbook for Highschool - Eastern Townships Resource Centre (ETRC) (2019)

Update - Leading English Education and Resource Network (LEARN) (2016)

Year-End Report - Leading English Education and Resource Network (LEARN) (2016)
The Leading English Education and Resource Network (LEARN) is a non-profit organization that serves the public, private, anglophone and aboriginal Youth and Adult Education sectors of Québec. We bring together the expertise and efforts of educators, students, parents and partners in our community to cultivate success for all learners.

June 12, 2014 - Leading English Education and Resource Network (LEARN) (2014)

Community Learning Centres : Changing Lives and Communities Annual Report of Activities - Leading English Education and Resource Network (LEARN) (2013)
This year the 37 Community Learning Centres across Quebec worked collaboratively with more than 700 local, regional, provincial, and national partners, to leverage in excess of $3 million of in-kind services and resources to serve their schools and communities. CLCs are doing more than just leveraging resources; they are changing lives and communities. They serve as a place for education and community development, and have become an important part of collaborative community change efforts. The stories and best practices highlighted in this annual report capture the essence of the initiatives being implemented by CLCs to achieve change and progress in English speaking communities across Quebec. Highlights of the activities undertaken in 2012-2013 begin with how one of our most important stakeholder groups, our teachers, are engaging with our initiative. The Community-Based Learning approach is just one example of the many strategies CLCs are adopting to impact students and develop a culture of lifelong learning. This year’s activities also included many examples of in-school and after-school activities in which CLC students are learning about incorporating healthy living options into their lives as well learning about aboriginal culture and building relationships between aboriginal and non-aboriginal communities. CLCs mobilize community and partner support to address current and important needs in our schools, including improving school climate and reducing bullying. Their activities for adults and seniors demonstrate to students that learning truly is a lifelong process. Engaging parents before their children have even entered school and continuing to find ways to connect and support parents throughout school life is an ongoing and important part of our work.

June 13, 2013 - Leading English Education and Resource Network (LEARN) (2013)

Update - Leading English Education and Resource Network (LEARN) (2012)

Wild Berrylicious : Youth School Kit - Coasters Association (2012)

A Brief to the Commission for the Estates General on Education from Quebec Federation of Home and School Associations - Quebec Federation of Home and School Associations (QFHSA) (1995)
One of the stated aims of the Home and School movement is to assist in forming public opinion favourable to educational reform and to the advancement of the education of the child. Thus we are pleased to be able to submit this brief to the Commission for the Estates General on Education. This brief is presented in both French and English. However, these two versions are not direct translations, but have been written independently based on the same input and the same discussions. Care has been taken to examine both versions to ensure that their message is the same.

Quebec Home & School News - Quebec Federation of Home and School Associations (QFHSA) (1993)

Quebec Home & School News - Quebec Federation of Home and School Associations (QFHSA) (1992)

Quebec Home & School News - Quebec Federation of Home and School Associations (QFHSA) (1992)

Quebec Home & School News - Quebec Federation of Home and School Associations (QFHSA) (1989)

A Report to Superior Council of Education on the State and Needs of Education in 1985 from Quebec Federation of Home and School Associations - Quebec Federation of Home and School Associations (QFHSA) (1985)
Quebec Federation of Home and School Associations (QFHSA), founded in 1944 is an independent voluntary parental organization representing approximately six thousand families, mainly within the English speaking communities throughout the province. Parent volunteers are active within local Home and School associations, the national level through the Canadian Home and School Parent Teacher Federation. One of the stated aims of the Home and School movement is to assist in forming public opinion favourable to reform and the advancement of the education of the child. thus we are pleased to submit this report on the state and needs of education as requested by the Superior Council of Education.

A Statement from Quebec Federation of Home and School Associations to the Superior Council of Education on the State of the Condition of Teaching in the Province of Quebec - Quebec Federation of Home and School Associations (QFHSA) (1984)
Quebec Federation of Home and School Associations (QFHSA) is a parent group, working as volunteers at the school, provincial and national levels. QFHSA takes particular pride in the fact, that over the last forty years, parents, as volunteers, have seconded the schools' efforts to provide assistance in areas of school life, to upgrade or enhance the school's environment and, thereby, benefit the students. As an adjunct to direct involvement at the school level, though its resolutions addressed, over the years, to various levels involved in the educational process, QFHSA has pinpointed areas its members felt needed either more funding, changing, support, introduction, etc., as the case may be. These will be referred to specifically later on.

Brief to the Minister of Education Regarding the Cumulative School Record Presented by Quebec Federation of Home & School Associations - Quebec Federation of Home and School Associations (QFHSA) (1974)
The Quebec Federation of Home & School Associations, representing over 12,000 families who are members of local associations in schools or groups of schools, in preparing this Brief has received comments and assistance from associations on the Island of Montreal, the south and north shore , Quebec City, Hull, Gaspe and the Eastern Townships and also from a number of school committees .

Brief on Teacher Classification Presented by Quebec Federation of Home & School Associations to Commission of Study on the Classification of Teachers - Quebec Federation of Home and School Associations (QFHSA) (1974)
The Quebec Federation of Home & School Associations at its Annual General Meeting held in May 1971, passed two resolutions on the issue and conflict arising in respect of Teacher Classification to be directed to the Minister of Education.

Brief on Bill 62 to the Education Committee of the National Assembly of the Province of Quebec - Quebec Federation of Home and School Associations (QFHSA) (1970)
The Quebec Federation of Home and School Associations, formerly the Quebec Federation of Protestant Home and School Associations (hereinafter referred to as "Quebec Federation") wishes to present the Education Committee of the National Assembly of the Province of Quebec with the views of its membership on the proposed Bill 62.

In Survival Mode : Adult Education Teachers Experience of Covid-19 and their Use of Digital Technologies - Bowles, Emilie